Biomechanical and clinical evaluation of interlocking hip screw in Pauwels Ⅲ femoral neck fractures: A comparison with inverted triangle cannulated screws - Zhang, Jian; Jiang, Haozheng; Dai, Wei; Hersi, Salad Abdirahman; Chun tien chui wan Cheong, John; Chu, Zhenchen; Lou, Zhiyuan; Zhang, Deqiang; Liu, Changjian; Tian, Kang; Tang, Xin (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: To compare biomechanical and clinical properties of the novel internal fixation Interlocking Hip Screw (IHS) and conventional inverted triangle cannulated screws (ITCS) for treatment of Pauwels Ⅲ femoral neck fractures. Methods: Twenty synthetic femurs were osteotomized to simulate 70° Pauwels Ⅲ femoral neck fractures and randomly divided into two groups: Group IHS and Group ITCS. Specimens were loaded in quasi-static ramped and cyclical compression testing in 25° adduction to analyze for axial stiffness, failure load, and interfragmentary displacement. 21 matched patients with Pauwels Ⅲ femoral neck fracture who received closed reduction and internal fixation from January 2020 to January 2021 in both Group IHS and Group ITCS. Demographic data, time to surgery, operating duration, intraoperative blood loss, number of fluoroscopies, length of hospital stay, fracture healing time, Harris Hip Score (HHS), the score of Visual Analogue Scale (VAS) and complications such as nonunion, avascular necrosis, and femoral neck shortening were compared. Results: All specimens in the two groups survived in the axial and cyclical compression test. The axial stiffness was significantly higher for Group IHS (277.80±26.58N/mm) versus Group ITCS (205.33±10.46N/mm), p<0.05. The maximum failure loading in Group IHS performed significantly higher than in Group ITCS (1400.48±71.60N versus 996.76±49.73N, p<0.05). The interfragmentary displacement of the cyclic loading test for Groups IHS and Group ITCS was 1.15±0.11mm and 1.89±0.14mm, respectively, p<0.05. No significant difference was found in terms of demographic data, time to surgery, intraoperative blood loss, length of hospital stay and the occurrence of nonunion and avascular necrosis between groups. Shorter operating duration and fewer intraoperative fluoroscopic views were noticed using IHS compare to ITCS, p<0.05. The HHS was 72.14±5.76 and 86.62±5.01 in Group IHS, and was 67.29±5.27 and 81.76±5.13 in Group ITCS at 3-month and 6-month follow-up, respectively, p<0.05. The magnitude of femoral neck shortening was significantly lower in Group IHS compared to Group ITCS (4.80±1.03mm versus 5.56±1.21mm, p<0.05). Conclusions: Our study demonstrated that IHS provided better biomechanical and clinical performance due to its unique biological and biomechanical mechanisms, compared with ITCS. Thus, IHS is a feasible alternative to ITCS for the fixation of Pauwels Ⅲ femoral neck fractures.